Plan for the management of cultural heritage in Mexico: the experience of the historical center of Oaxaca de Juarez - Gutiérrez Chira, Karina (2019)
The Historic Center of Oaxaca de Juárez is one of the ten historic Mexican centers inscribed by Unesco as World Heritage Sites. Due to this inscription, a greater interest in the management, conservation and diffusion of the cultural wealth of this area has been generated, which is why the Partial Plan of Conservation of the Historic Center of Oaxaca de Juarez of 1997 was elaborated and proposed as a participatory and concerted instrument that shows the problems of the time and offers some strategies as a solution. However, the objectives of this plan were not fully completed. Today, there are new challenges to face in the historic center of Oaxaca de Juarez that manifest the need for an update of the plan or the creation of other management and ordering tools for its center. It is necessary to learn from this experience to be able to make points of comparison with the various types of historic centers that exist in Latin America.